Synthesis of spiro chromanone sandwiched 15, 16, 18 membered (Z)-dioxo cycloalkenes by ring closing metathesis and homodimers of 8-allyl-7-((6-bromoalkyl) oxy) spirochroman-4-ones by cross metathesis. Issue 5 (4th March 2022) - K., Prathima; Ashok, D.; Sarasija, M.; Dharavath, Ravinder; Utkoor, Umesh Kumar; Lakshmi, V. V. S.; Ganji, Sai Krishna; Sripadi, Prabhakar
Abstract: Novel spiro chromanone sandwiched 15, 16, 18 membered ( Z )-1, 7-dioxo cycloalkenes by Ring Closing Metathesis (RCM) and homodimers of 8-allyl-7-((6-bromo alkyl)oxy) spirochroman-4-ones by Cross Metathesis (CM) were synthesized from simple starting materials 2, 4 dihydroxy acetophenone, allyl bromide, and dibromo alkanes. Spiro chromanone is chosen as the core moiety to be incorporated owing to its medicinal and pharmacophoric properties. The concept of molecular hybridization was adopted for the synthesis of compounds 18–26 using Ring Closing Metathesis as a key step. Intermediates 6, 7, 8 were alkylated with dibromo alkanes to obtain the substrates for RCM and CM, respectively. The dimer dienes 9–17 were made to undergo RCM and the bromo alkyl intermediates 27–34 were made to undergo CM to get homodimers 35–42 . Graphical Abstract: UF0001